2013
DOI: 10.1002/anie.201308385
|View full text |Cite
|
Sign up to set email alerts
|

A Di‐Substituted Boron Dication and Its Hydride‐Induced Transformation to an NHC‐Stabilized Borabenzene

Abstract: Give me a B: A stepwise chloride abstraction of [Cp*BCl2(IMes)] resulted in the linear di‐substituted boron dication [Cp*B(IMes)]2+. The hypercoordinated boron dication, stabilized in the pentagonal pyramidal [C5B]2+ cluster, reacts with superhydride to yield the N‐heterocyclic carbene‐stabilized borabenzene, [C5Me5B(IMes)] (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 83 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…With the aid of NHCs, Chiu et al were able to stabilize and structurally characterize the dicationic boron species 217 (Scheme ). It was synthesized upon stepwise treatment of [Cp*BCl 2 (IMes)] with AlCl 3 as chloride ion scavenger in chlorobenzene. Compound 217 (C NHC –B bond distance 1.558(4) Å) features a sharp signal at −49 ppm in the 11 B NMR spectra.…”
Section: Nhc Complexes Of Main Group Elementsmentioning
confidence: 99%
“…With the aid of NHCs, Chiu et al were able to stabilize and structurally characterize the dicationic boron species 217 (Scheme ). It was synthesized upon stepwise treatment of [Cp*BCl 2 (IMes)] with AlCl 3 as chloride ion scavenger in chlorobenzene. Compound 217 (C NHC –B bond distance 1.558(4) Å) features a sharp signal at −49 ppm in the 11 B NMR spectra.…”
Section: Nhc Complexes Of Main Group Elementsmentioning
confidence: 99%
“…In addition, a terminal borylene complex containing an h 5 -Cp* ligand, namely [(h 5 -Cp*)BFe(CO) 4 ], 22 was described by Cowley. In addition, examples of dicationic [(h 5 -Cp*)B(L)] 2+ species have been reported. 23,24 For group 14 derivatives, the heavier elements form metallocenes(II) [(h 5 -Cp*) 2 E] (E = Si, 25 Ge, 26 Sn, 26 Pb 27 ) and half-naked E(II) cations of the form [(h 5 -Cp*)E] + (E = Si, 28 Ge, 26 Sn, 29 Pb 30 ) (Figure 1B). Interestingly, a carbon dication [C 6 (CH 3 ) 6 ] 2+ , recently reported by Malischewski and Seppelt, 31 could be described as an h 5 -Cp*-bonded carbon dication [(h 5 -Cp*)CCH 3 ] 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…Thermolysis of boracyclohexadiene boronium ion affords the NHC-stabilized borabenzene . Our group has also demonstrated that structural rearrangement of a hypercoordinated boron dication ([Cp*B-IMes] 2+ , [ 1 ] 2+ ) to a planar neutral borabenzene ( 2 ) could be initiated through the addition of Li­[Et 3 BH] (Scheme c) . Similar boron atom insertion to the Cp* ring has been observed only within the coordination sphere of transition metals .…”
Section: Introductionmentioning
confidence: 55%